1998
DOI: 10.2139/ssrn.141216
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Effects of U.S. Food Aid

Abstract: Although food aid may have important medium-to long-term effects, there is a glaring absence of empirical research on food aid dynamics. This paper applies vector autoregression methods to data from 18 countries over the period 1961-95.We find evidence that food aid has a pronounced J-curve effect on recipient country per capita commercial food imports but only negligible negative effects on recipient country per capita food production. The commercial export gains are primarily enjoyed, however, by the dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 13 publications
1
29
1
Order By: Relevance
“…The dynamic impacts of food aid on the consumption patterns of low-income people, human capital, asset formation, and overall development implications were emphasized by Mellor (1980), Deaton (1980), Bezuneh et al (1988), Deaton (1997), Hoffman et al (1994), Barrett (1998), and Barrett et al (1999). Cathie's (1991) approach to modeling food aid impacts in Botswana recognized the limitation of available data and the conceptual underpinnings of theory.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic impacts of food aid on the consumption patterns of low-income people, human capital, asset formation, and overall development implications were emphasized by Mellor (1980), Deaton (1980), Bezuneh et al (1988), Deaton (1997), Hoffman et al (1994), Barrett (1998), and Barrett et al (1999). Cathie's (1991) approach to modeling food aid impacts in Botswana recognized the limitation of available data and the conceptual underpinnings of theory.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, he found that in cases where food aid complement domestically produced cereals, food aid imports encourage additional local food production. More recent studies by Barrett et al (1999) and Abdulai et al (2005) provide further evidence indicating the lack of significant disincentive production effect in recipients' economies. Lowder (2004) also shows from a cross-country panel data analysis that there is no significant disincentive effect on production, irrespective of whether programme or targeted food aid was analysed.…”
Section: Food Aid Effects On Recipient's Local Food Marketsmentioning
confidence: 87%
“…The first empirical food aid impact study that explored dynamic issues was by Lavy (1990) who examined the validity of the claims that food aid allocations create production disincentive effects. Subsequent studies that considered VAR modelling techniques includes: Barrett (1998), Barrett et al (1999) and Donovan et al (1999). More recent studies extended dynamic time series models to panel data and also applied generalised methods of moments (GMM) modelling techniques (Quisumbing, 2003;Lowder, 2004;Abdulai et al, 2005).…”
Section: Dynamic Times Series Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food aid has been studied intensively by economic researchers, from its effectiveness at consumption smoothing (see Srinivasan 1989;Gupta, Clements, and Tiongson 2004) to its possible disincentive effects on local food production and its spillovers on international food trade (see Isenman and Singer 1977;Barrett, Mohapatra, and Snyder 1999;Barrett 2001;Abdulai, Barrett, and Hoddinott 2005) and its diversion away from the most needy (see Jayne et al 2001). We provide a very different perspective on food aid: its strategic use to minimize armed conflict.…”
Section: Related Literaturementioning
confidence: 99%